720 ED physician and nurse experience in diagnosising and reporting paediatric abuse-related Trauma in China. (1st September 2016) - Zhu, Huiping; Shao, Jianbo; Peng, Jin; Yu, Chuanhua; Yao, Wenyan; Yao, Hongyan; Shi, Junxin; Xiang, Huiyun
Abstract : Background: Child abuse and neglect are serious problems around the world. However, little research has been done in China to describe the burden and characteristics of abuse-related trauma among Chinese children. It also remains unknown about experience of emergency department physicians and nurses in treating and reporting suspected abuse-related trauma. The objectives of this study were to 1) examine how Chinese physicians and nurses identify and report physical child abuse; and 2) examine whether they are aware of any official policies and guidelines regarding physical child abuse. Methods: We conducted a questionnaire survey among physicians and nurses who work at emergency departments (EDs) of 15 large children's hospitals in China. The questionnaire included demographic information, knowledge and past experiences of identifying and reporting physical child abuse and abusive head trauma, standardised practice protocols, and perceived major obstacles of reporting physical child abuse. Results: Our study collected 304 completed questionnaires, 154 from physicians and 150 from nurses. Physicians and nurses reported that 40.1% of them encountered children in their practice whom they suspected were a victim of physical child abuse. However, only 10.2% asked caregiver and noted in the medical records and 9.9% reported the child abuse. The majority of physicians (86.3%) and nurses (86.0%) were not aware of any standardised protocol for identifying and reporting physical child abuse in China. Only 3.6% of ED physicians and nurses have ever received training in how to identify and diagnose physical child abuse. Conclusions: Abuse-related trauma is likely underreported and there is a great need to train medical care professionals in diagnosing and reporting child physical abuse in China.